The Use of E-CRM in Controlling and Developing Sales Systems for Cosmetik Stores Success Together - Andriani, Asih; Nofriadi, Nofriadi; Santoso, Santoso (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Toko Cosmetik Sukses Bersama is an individually owned small business store that has been established since 2021. The brands of cosmetic products marketed include Hanasui, Wardah, Emina, Implora, Pixy, Kahf, Ms Glow, and OMG. Cosmetics are used to enhance physical appearance and have a positive impact on a person's self-confidence. In the last period of time, the large number of competition in marketing cosmetic products that occurred made the store's sales experience a decline in sales which resulted in a decrease in revenue. Making sales reports at Toko Cosmetik Sukses Bersama is still done by bookkeeping which allows recording errors. Shop owners still visit small shops directly or receive orders via phone calls. Therefore, the use of E-CRM strategies will provide convenience for customers and sales. By doing 3 CRM strategy efforts such as Acuiring (Getting Customers), Enchancing (Strengthening Relationships), Retaining (Maintaining Customers). So that by implementing the E-CRM strategy at Toko Cosmetik Sukses Bersama can increase cosmetic sales and bring in new customers.